A noção de sujeito em linguística textual: práticas (con)textuais e identitárias das dissidências sexuais e de gênero - Matos, Samuel de Souza (2024)
In contemporary society, digital textual practices expand sociopolitical and ideological disputes (Van Dijk, 2015, 2018) of sexual and gender dissent activism (Colling, 2016; Borba, 2020a). As discursive arenas of online self-representation (Barton; Lee, 2015), digital environments propagate multiple strategies for stabilizing and/or destabilizing the identities of these minority social subjects. In this sense, the study of the “subject”, combined with questions of “context” and “identity”, in Textual Linguistics (TL), calls for textual analyzes that go beyond the cotextual and local dimension of enunciative activities (Benveniste, 1989, 1995). From this perspective, this doctoral thesis seeks to answer two research questions: i) what dialogue can be established between sociocognitivism, the post-identity paradigm and the notion of “subject” in contemporary TL, with a view to studying (con)texts of sexual and gender dissent?; ii) what gender and sexuality identity practices are (re)elaborated by these minority subjects in the face of cis-heteronormativity? Through a qualitative approach (Prodanov; Freitas, 2013), with a descriptive-interpretivist bias (Cavalcante et al., 2016), the objective of the thesis is to understand, in the light of the dialogue between textual, socio-cognitive and queer approaches, identity practices of dissident gender and sexuality subjects, in a digital epistemic community, with a view to repositioning the epistemological-methodological frameworks of TL. To this end, notions of subject (Cavalcante et al., 2019; Mondada; Dubois, 2003; Butler, 2015), models of context (Van Dijk, 2020) and identity practice (Butler, 2002; Van Dijk, 2013), from a procedural, anti-essentialist and integrationist perspective. In turn, the research universe covers a sample of 64 autobiographical interviews, available on the Pheeno TV channel, on the YouTube platform, between June 2022 and May 2023. Thus, the elaboration of an epistemological-methodological map directs the analyzes of the corpus (six interviews) based on two procedures: i) description of linguistic-discursive strategies; ii) interpretation of sociocognitive, interactional, cultural, political and historical processes. In a critical and ethicalpolitical inflection (Rajagopalan, 2003; Ferreira; Rajagopalan, 2016) of the theoreticalanalytical constructs and the phenomena investigated, the results point, firstly, to a multidisciplinary dialogue between socio-discursive perspectives via processes of assimilation and of miscegenation. Secondly, the (con)textual and identity practices, constructed by dissident subjects, signal stylized corporeal-discursive acts through activities of indexicality and recontextualization of subjectivation experiences. In this dynamic, the textual configuration is partially influenced by conflicts and ideological alignments between different epistemic communities. So, on the one hand, there is the reinforcement of macrosocial normalization processes, and, on the other, friction with strategies of destabilization of the sex/body/gender/desire/practice matrix of intelligibility, through interrelations between body, gender, sexuality, race, age, profession, bi/homophobic violence and ageism, linked to family, religious, educational and media discursive domains. Thus, social meanings of identity stability and intelligibility predominate, as well as the reiteration of discriminatory practices, in situated discursive activities. Therefore, it is possible to contribute, based on this politicalepistemological proposal, to: i) the expansion of the theoretical-analytical method of (con)texts and identities produced by sexual and gender dissent; ii) the expansion of the perception of identity (re)constructions of this social group, in cyberactivism practices, as a possibility of reengagement in their political actions.